Analisis Peningkatan Kualitas Infrastruktur Air Limbah Domestik Secara Berkelanjutan Pada Kawasan Maritim Kota Makassar - Ariani, Ayu; Burhanuddin, Fathurrahman; Praja, Soemitro Emin (Universitas Muslim Indonesia, 2025)
This study examines domestic wastewater infrastructure in the slum area of Barombong Village, Makassar City. Gray water drains are drained directly into the soil without a treatment process, while black water management is on top of stagnant soil, increasing the risk of contamination. The high density of buildings causes the discharge of grey water directly into the river to pollute the water and soil. The analysis method used to improve the quality of domestic wastewater infrastructure is a weighting analysis with scoring based on the classification of sustainability levels aimed at determining the level of sustainability of infrastructure at the research site. The Analytical Hierarchy Process (AHP) method is used to determine the direction of sustainable development of gray water and black water infrastructure. The results show that the sustainability level of grey water in zones 1, 2, 3 and 5 is categorized as low, while zone 4 is categorized as moderate. The sustainability level of black water in zones 1, 2, 3 and 4 is categorized as moderate, while zone 5 is low. The direction of sustainable black water WWTP infrastructure in zones 1, 2, and 3 is the construction of communal septic tanks, zone 4 biogas digesters, and zone 5 individual septic tanks. Meanwhile, the direction of grey water infrastructure in zones 1, 2, and 3 is the construction of wetlands, zone 4 anaerobic biofilters, and zone 5 grey water recycling.